MAINTAINING GOOD HEALTH DEMANDS A COMBINATION OF HABITS, EXERCISE, AND LIFE CYCLE STRATEGY. - Dr. Yuwraj Shrivastava*Dr. Vinod Kumar (Chelonian Research Foundation, 2023)
The key components of health are having happy parents, a happy home, a healthy diet, a clean environment, and a fulfilling employment in a nice neighborhood. A beautiful, smoothly running car is the product of adequate maintenance, just as health is the reward for taking care of the body. Health is not just the absence of disease; rather, it encompasses the totality of one's physical, mental, and social well-being, together with the enjoyment of the best possible standards of health. Every person has a fundamental right to health, which is also essential to achieving peace and security. A healthy individual is one who has the capacity to think clearly and execute any type of work. This subject will continue Health care needs, causes of health issues, and recommendations for improving human health. Keywords: Diet, Mental Health Exercise, Habits, and life cycle